DISORDERS HOMEOCINESIS IN PERITONITIS AND ITS CORRECTION - Maxmuda N. Agzamova; Khasan M. Jafarov; Farhod D. Ortiqboyev (Central Asian Journal of Medicine, 2024)
Objective. The study of the characteristics of peritonitis in people of working age with the establishment of the current state of the microflora and the development of treatment methods. Materials and methods. The study was conducted in 150 patients (20-60 years) with various forms of peritonitis. Results. The combined use of thymalin, furacillin solution and lymphotropic antibiotic therapy contributed to the rapid elimination of surgical infection.